MicroRNA-33 Controls Adaptive Fibrotic Response in the Remodeling Heart by Preserving Lipid Raft Cholesterol. Issue 5 (3rd March 2017) - Nishiga, Masataka; Horie, Takahiro; Kuwabara, Yasuhide; Nagao, Kazuya; Baba, Osamu; Nakao, Tetsushi; Nishino, Tomohiro; Hakuno, Daihiko; Nakashima, Yasuhiro; Nishi, Hitoo; Nakazeki, Fumiko; Ide, Yuya; et al.
Abstract : Rationale: : Heart failure and atherosclerosis share the underlying mechanisms of chronic inflammation followed by fibrosis. A highly conserved microRNA (miR), miR-33, is considered as a potential therapeutic target for atherosclerosis because it regulates lipid metabolism and inflammation. However, the role of miR-33 in heart failure remains to be elucidated. Objective: : To clarify the role of miR-33 involved in heart failure. Methods and Results: : We first investigated the expression levels of miR-33a/b in human cardiac tissue samples with dilated cardiomyopathy. Increased expression of miR-33a was associated with improving hemodynamic parameters. To clarify the role of miR-33 in remodeling hearts, we investigated the responses to pressure overload by transverse aortic constriction in miR-33–deficient (knockout [KO]) mice. When mice were subjected to transverse aortic constriction, miR-33 expression levels were significantly upregulated in wild-type left ventricles. There was no difference in hypertrophic responses between wild-type and miR-33KO hearts, whereas cardiac fibrosis was ameliorated in miR-33KO hearts compared with wild-type hearts. Despite the ameliorated cardiac fibrosis, miR-33KO mice showed impaired systolic function after transverse aortic constriction. We also found that cardiac fibroblasts were mainly responsible for miR-33 expression in the heart. Deficiency of miR-33 impaired cardiac fibroblast proliferation, which was considered to be caused by altered lipid raft cholesterol content. Moreover, cardiac fibroblast–specific miR-33–deficient mice also showed decreased cardiac fibrosis induced by transverse aortic constriction as systemic miR-33KO mice. Conclusion: : Our results demonstrate that miR-33 is involved in cardiac remodeling, and it preserves lipid raft cholesterol content in fibroblasts and maintains adaptive fibrotic responses in the remodeling heart. Abstract : Supplemental Digital Content is available in the text.